Indigenous autonomy and the legacy of neoliberal decentralization in plurinational Bolivia. Issue 1 (2nd January 2018) - Alderman, Jonathan
ABSTRACT: This article examines the legacy of 1990s' neoliberal decentralization reform in shaping an indigenous autonomy project in Bolivia. It focuses on the municipality of Charazani, which is in the process of becoming an Indigenous Autonomy, or Autonomía Indígena Originario Campesina (AIOC), examining the local origins of the autonomy project, and the reasons why it has stalled. To do so, I refer to political projects of indigenous authorities in Charazani in the early 1990s, to take power locally as a bloc and disconnect themselves from the power of the local townspeople by challenging fictive kinship ties with them. The article explores the role that local devolved forms of government have had in producing competition among indigenous communities since the 1990s and the effect on the formulation of a joint project for indigenous autonomy. The establishment of indigenous autonomy requires cooperation and agreement among the communities of the municipalities undergoing conversion to an AIOC. This article posits that internal disagreements, which threaten autonomy, are closely entwined with the neoliberal structures upon which local governance is based (and from which AIOCs are supposed to spring), which encourage intercommunity competition for scarce resources.